Buharî'nin Sahîh'inde Re'y Ehline İtiraz Ettiği Bazı Meseleler - Eren, Mehmet (Dinî araştırmalar, 2003)
al-Bukhârî has mainly two purposes in the compilation of al-Sahih: the first one is to compile the ahâdîth he regarded as sahih (sound hadith) and the second one is to put forward the legal injunctions out of these ahadith with the subtle points full of wisdom. In al-Sahih, there have been largely legal opinions in the titles of al-bâb. In some of them, al-Bukhârî has examined the opinions of al-Hanafiyyun known as Ahl al-Ra’y and criticized them from different aspects. It has been seen that the opinions beginning with the term Qâla ba‘d al-nâs belong to Abu Hanifa and they have been included in the content of al-Sahih in order to be rejected. The fact that this term repeated twenty-five times in al-Sahih has been mentioned fourteen times in the Chapter al-Hiyal shows that all of the Hiyal subjects was a matter of discussion between al-Bukhâri and the Hanafiyyûn. In my opinion, al-Bukhârî having the convinction that he comprehended the Book (al-Qur’an) and the Sunnah, has attempted to get legal injunctions out of these two sources. In addition, al-Bukhârî was very familiar with the opinions of al-Sahâba (Companions of the Prophet Muhammad) and al-Tâbiûn (the next generation after the Sahâba) scholars alongside with the opininions of previous grand jurists, so he received great support from their views